Competitiveness of three biocontrol candidates against ochratoxigenic Penicillium nordicum under dry-cured meat environmental and nutritional conditions. Issue 2 (February 2021) - Álvarez, Micaela; Núñez, Félix; Delgado, Josué; Andrade, María J.; Rodríguez, Mar; Rodríguez, Alicia
Abstract: The environmental conditions during the ripening of dry-cured meats and their nutritional composition promote the colonisation of their surface by Penicillium spp., including P. nordicum producer of ochratoxin A (OTA). The objective of this work was to study the competitiveness of three potential biocontrol candidates ( Debaryomyces hansenii FHSCC 253H, Enterococcus faecium SE920 and Penicillium chrysogenum CECT, 20922) against the ochratoxigenic P. nordicum FHSCC4 under environmental and nutritional conditions simulating the ripening of dry-cured meat products. For this, the nutritional utilisation pattern, niche overlap index (NOI), interactions by dual-culture assays and OTA production were determined. The number of carbon sources (CSs) metabolised depended on the microorganism and the interacting water activity (aw ) x temperature conditions. The number of CSs utilised by both filamentous fungi was quite similar and higher than those utilised by D. hansenii and E. faecium . The yeast isolate metabolised a number of CSs much larger than the bacterium. The NOI values showed that, in general, P. nordicum nutritionally dominated E. faecium and D. hansenii regardless of the environmental conditions evaluated. The relationship between the toxigenic and non-toxigenic fungal isolates depended on the aw x temperature combinations, although in none of the conditions a dominance of P. nordicum was observed. According to the interaction assays, both D. hansenii and P. chrysogenum decreased the growth of P. nordicum . The effect of D. hansenii could be attributed to the production of some extra-cellular compounds, while the action of P. chrysogenum is likely related to nutritional competition. In addition, both P. chrysogenum and D. hansenii reduced the OTA levels produced by P. nordicum . The effect of the yeast was more pronounced decreasing the concentration of OTA at quantities lower than the limit established by the Italian legislation. Therefore, P. chrysogenum and D. hansenii can be suggested as biocontrol candidates in the manufacture of dry-cured meat products. Highlights: Penicillium chrysogenum and Debaryomyces hansenii reduced the growth of P. nordicum . D. hansenii showed dominance at distance over P. nordicum . The action of P. chrysogenum over Penicillium nordicum is based on nutritional competition. P. chrysogenum and D. hansenii limited OTA production by P. nordicum . P. chrysogenum and D. hansenii can be proposed as biocontrol agents in dry-cured meats.